ANTI-DENGUE TYPE 2 VIRUS ACTIVITIES OF ZINC (II) COMPLEX COMPOUNDS WITH 2-(2,4 -DIHYDROXYPHENYL)-3,5,7-TRIHYDROXYCROMEN-4-ONE LIGANDS IN VERO CELLS - Sucipto, Teguh Hari; Setyawati, Harsasi; Churrotin, Siti; Amarullah, Ilham Harlan; Sumarsih, Sri; Wardhani, Puspa; Aryati, Aryati; Soegijanto, Soegeng (Indonesian Journal of Tropical and Infectious Disease, 2019)
Dengue virus (DENV) is a disease that is transmitted through Aedes aegypti and Aedes albopictus mosquitoes, and is spread in tropical and sub-tropical regions. Now, dengue or antiviral vaccines for humans do not yet exist, but there are great efforts to achieve this goal. Complex compounds are reported to fungicidal, bactericidal and antiviral activity. Antiviral activity against DENV is an important alternative to the characterization and development of drugs candidate. The purpose of this study was to study zinc(II) compounds with 2-(2,4-dihydroxyphenyl)-3,5,7-trihydroxycromen-4-one ligand on DENV-2 replication in Vero cells. Vero cell lines (African green monkey kidney) was used in this study, maintained and propagated in Minimum Essential Eagle Medium containing 10% fetal bovine serum at 37°C in 5% CO2. The activity of dengue virus was carried out by enzyme-immunosorbent assay (ELISA) method and CellTiter96® Non-Radioactive Proliferation. The value of activity inhibition (IC50) of complex compounds with variations of mol metal: ligand 1:2, 1:3, and 1:4 against dengue virus type 2 (DENV2) was 2.44 Î¼g/ml, 2.75 Î¼g/ml, respectively and 2.00 Î¼g/ml, also the toxicity value (CC50) of complex compounds with variation mol metal: ligand 1:4 for Vero cells is 3.59 Î¼g/ml. The results of this study were indicate that these properties have been shown to inhibit anti-dengue type 2 virus (DENV-2), but are also toxic in Vero cells. Including previous study about complex compound interaction with dengue virus type 2 activity, Zn(II) more reactive compound then Cu(II), and Co(II). The comparison with Cu(II) complex compound, it has been revealed that Co(II) and Zn(II) is more toxic, was found to be nontoxic to human erythrocyte cells even at a concentration of 500 Î¼g/ml.